Access-A research agenda for Edinburgh festivals - Carlsen, Jack; Ali-Knight, Jane; Robertson, M. (Cognizant Communication Corporation, 2007)
Festivals and events have assumed a prominent place in the social and economic fabric of Edinburgh, to a point where it now enjoys a reputation as a leading festival and event destination. In Edinburgh, as in other festival destinations, most of the research and evaluation effort has been concerned with "proving" the economic benefits of individual events. The limitations of focusing on narrow economic outcomes are now widely recognized in terms of the comparability, reliability, and utility of the estimates produced. While the attention of stakeholders has been on economic benefits, the very important cultural, community, and social benefits have been overlooked. Important issues such as engagement with the arts, community, cultural, social, and stakeholder benefits and disbenefits produced have yet to be researched in any systematic way. This article offers a comprehensive research agenda for key festivals in Edinburgh and acts an introduction to this special issue. The research agenda is based on published articles (inclusive of those in this volume), existing strategies and documentation, and the editors' knowledge of and engagement with the Edinburgh festival community. The agenda will be of interest to the numerous festivals and events stakeholders in Edinburgh as well as other destinations that are seeking to understand the social and cultural, as well the economic, dimensions of festivals.